In-vitro characterization of novel and functional regulatory SNPs in the promoter region of IL2 and IL2R alpha in a Gabonese population - Huang Xiangsheng; Kühne Vera; Kun Jürgen F J; Soboslay Peter T; Lell Bertrand; TP Velavan (BMC, 2012)
Abstract Background The selection pressure imposed by the parasite has a functional consequence on the immune genes, leading to altered immune function in which regulatory T cells (Tregs) induced by parasites during infectious challenges modulate or thwart T effector cell mechanism. Methods We identified and investigated regulatory polymorphisms in the immune gene IL2 and its receptor IL2R alpha (also known as CD25) in Gabonese individuals exposed to plentiful parasitic infections. Results We identified two reported variants each for IL2 and its receptor IL2R alpha gene loci. Also identified were two novel variants, -83 /-84 CT deletions (ss410961576) for IL2 and -409C/T (ss410961577) for IL2R alpha. We further validated all identified promoter variants for their allelic gene expression using transient transfection assays. Three promoter variants of the IL2 locus revealed no significant expression of the reporter gene. The identified novel variant (ss410961577C/T) of the IL2R alpha revealed a significant higher expression of the reporter gene in comparison to the major allele (P<0.05). In addition, the rs12722616C/T variant of the IL2R alpha locus altered the transcription factor binding site TBP (TATA box binding protein) and C/EBP beta (CCAAT/enhancer binding protein beta) that are believed to regulate the Treg function. Conclusions The identification and validation of such regulatory polymorphisms in the immune genes may provide a basis for future studies on parasite susceptibility in a population where T cell functions are compromised.